Genetic and cytogenetic studies of four glycolytic enzymes in Drosophila melanogaster: aldolase, triosephosphate isomerase, 3-phosphoglycerate kinase, and phosphoglucomutase. - Voelker, R.A.; Ohnishi, S.; Langley, C.H. (Biochemical Genetics, 1979)
Four glycolytic enzymes in Drosophila melanogaster have been genetically and/or cytogenetically mapped. The structural gene for aldolase (Ald) has been genetically mapped to 3-91.5 and cytogenetically localized to 97A-B. Tpi, the structural gene for triosephosphate isomerase, has been genetically mapped to 3-101.3 and cytogenetically localized to 99B-E. Utilizing closer-flanking markers than the previous mapping, Pgk, the structural gene for 3-phosphoglycerate kinase, has been mapped to 2-5.9; cytogenetically it was found to lie in the interval between 22D and 23E3. The cytogenetic locataion of Pgm, the structural gene for phosphoglucomutase which has been located genetically at 3-43.4, was determined to be in 72D1-5.